Foreign exchange risk associated with debt: Application of the VaR approach to Morocco’s foreign debt portfolio - Nouhaila BELFATMI; Hicham OUAKIL (African Scientific Journal, 2024)
Abstract The aim of this article is to assess the exchange rate fluctuation risk associated with Morocco’s foreign debt, using the Value At Risk (VaR) method. To this end, daily data concerning the value of the Moroccan dirham against two major currencies used for debt, namely the Euro and the Dollar, Examination of the currency betas in the portfolio, together with VaR analysis, indicates that the US Dollar presents a significant risk. However, the euro could serve as a hedge against this currency risk for Morocco’s external debt portfolio. It is therefore strongly recommended to adopt a hedging policy to improve the efficiency of foreign exchange risk management. This involves specifying acceptable risk limits and appropriate hedging methods, using financial instruments such as forward contracts. These strategies make it possible to fix an exchange rate in advance to limit the impact of fluctuations on repayments. Keywords Foreign exchange risk, External public debt, Value at Risk, Morocco. Résumé Cet article vise à évaluer le risque de fluctuation des taux de change lié à la dette extérieure du Maroc en utilisant la méthode de la Value At Risk (VaR). Pour ce faire, des données quotidiennes concernant la valeur du Dirham marocain par rapport à deux devises majeures utilisées pour l’endettement, à savoir l’Euro et le Dollar, ont été analysées. L’étude se concentre sur la période après la flexibilisation, s’étendant du 01/01/2018 au 31/12/2021. L’examen des bêtas des devises dans le portefeuille, ainsi que l’analyse des VaR, indique que le dollar américain présente un risque significatif. Cependant, l’euro pourrait servir de couverture contre ce risque de change pour le portefeuille de la dette extérieure du Maroc. Par conséquent, il est fortement conseillé d’adopter une politique de couverture afin d’améliorer l’efficacité de la gestion du risque de change.. Cela implique d’indiquer d’une part les limites de risque acceptables et dans une autre part, les méthodes de couverture appropriées en recourant à des instruments financiers à titre des contrats à terme. Ces stratégies permettent de fixer un taux de change à l’avance pour limiter l’impact des fluctuations sur les remboursements. Mots clés : Risque de change, Dette publique extérieure, Value at Risk, Maroc